RANCANG BANGUN PROTOTIPE SOLAR CELL OFF GRID PADA LAMPU TAMAN OTOMATIS - Taufik, Muhammad; Asrul, Junaidi; Widia, Riza (Jurnal Ilmiah Poli Rekayasa, 2023)
This research aims to design an off-grid PLTS system for garden lighting based on IoT that is efficient and effective. This system will use IoT technology to control garden lights automatically based on light levels and time. This Off-Grid PLTS system will be designed based on the energy needs of garden lighting, solar panel and battery capacity, as well as a lighting control system. The results of research on solar panels tested for three days at 06:00 to 18:00 from the results of the first day of research obtained when the weather conditions were clear, the light level was obtained, namely 74000 lux with the power obtained 25.78 watts when charging the battery and when it rains, you get a light level of 800 lux with a charging power of 1.78 watts. From this it can be concluded that the effect of light intensity and weather on solar panels has an effect on charging the garden lamp battery. From the research results, charging the garden lamp battery with 12 V 35 Ah, the charging time is 21 hours 43 minutes with an average charging current of 1.92 A and battery discharge is obtained from research on the state of the automatic light, the battery discharge time is 19 hours 25 minutes with an average current 1.41A average. Bright light battery discharge time 18 hours 2 minutes with an average current of 1.55A.